Bismuth-213 and Actinium-225 – Generator Performance and Evolving Therapeutic Applications of Two Generator-Derived Alpha-Emitting Radioisotopes - Morgenstern, Alfred; Bruchertseifer, Frank; Apostolidis, Christos (Current Radiopharmaceuticals, 2012)
The alpha emitters 225Ac and 213Bi are promising therapeutic radionuclides for application in targeted alpha therapy of cancer and infectious diseases. Both alpha emitters are available with high specific activity from established radionuclide generators. Their favourable chemical and physical properties have led to the conduction of a large number of preclinical studies and several clinical trials, demonstrating the feasibility, safety and therapeutic efficacy of targeted alpha therapy with 225Ac and 213Bi. This review describes methods for the production of 225Ac and 213Bi and gives an overview of 225Ac/213Bi radionuclide generator systems. Selected preclinical studies are highlighted and the current clinical experience with 225Ac and 213Bi is summarized.
Keywords: Alpha emitter